Bioluminescence - Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid; Ahmad, Syahida; Tiow, Zhi Xuan; Tam, Xi Yuan; Islam, Tahzinul; Gomes, Gorakanage Ashen Indimal; Saad, Wan Zuhainis (Universiti Putra Malaysia Press, 2017)
Microcosm describes a miniature representation of a living or non-living thing. For example, there are miniature buildings, cars, furniture, dolls, mushrooms, flowers and plants. Microcosm bioluminescent mushrooms are miniatures of real mushrooms that produce light which is visible in the dark as a result of a biochemical reaction.